Hubungan Kepatuhan Minum Obat Dengan Kesembuhan Pasien Tuberkulosis Paru BTA Positif Di Puskesmas Delanggu Kabupaten Klaten - Aris Widiyanto (Interest : Jurnal Ilmu Kesehatan, 2017)
Abstract: Compliance Take Medicine The, Recovering, Positive Tuberculosis TB lung BTA. Object This research is to know the relationship of among compliance take medicine recovered is a patient of positive TB lung BTA in Puskesmas Delanggu of Sub-Province Klaten. The method this is analytic observational with the approach of research of cross-sectional. Sample in this research is patient of positive TB lung BTA which is registered in register TB Puskesmas Delanggu in the year 2012 which have followed the program DOTS and have finished its medication in the year 2013. The technique of Intake sample in this research is random sampling by sample counted 38 respondent. Technique analysis in this research is Chi-Square. Patient TB in Puskesmas Delanggu Klaten most obedient take medicine counted 25 responders (65,8%) and recovering of positive patient TB BTA most recovering counted 32 responders (84,2%). There is a relationship between compliance take medicine recovered is positive patient TB BTA in Puskesmas Delanggu Klaten. This Matter proven by value significant (P) 0.006 by = 5% hence P < 0.05. Compliance takes medicine to influence the story recovering of positive patient TB BTA in Puskesmas Delanggu Klaten.